Injury related risk behaviour: a Health belief model-based study of primary school students in a safe community in Shanghai. - Ling-Ling Zhang (Public Library of Science (PLoS), 2013)
Aim To explore the relationship between Health belief model (HBM) and children and adolescents' unintentional injury risk behavior, to add some useful information for injury prevention. Methodology We investigated injury related health risk behavior and health belief status of students at primary schools grade 3 to 4, in a Safe Community, in Shanghai. Self-administered injury questionnaires were used to investigate risk behavior of students and HBM factors. Principal findings The prevalence of risk behavior among students reported in this community was high. HBM scores showed differences between two groups of students classified by whether they had risk behavior or not. Self-efficacy was highly related with the status of socio-psychological behavior. Significance HBM has been widely used in explaining the disease-related behavior; however, it has been seldom used in injury-related behavior. The study demonstrated important relation of HBM to students' injury issues, and HBM could explain injury related behavior as well, especially for traffic injury-related behavior. When developing injury prevention strategies, we can take it into account.